Soil Health Management for Sustainable Agriculture Farm level experiences of Bighapur project - Tiwari, K N; Singh, S P; Kumar, Yogendra (Indian Farming, 2017)
Soil rejuvenation on the principle of IPNS will improve crop productivity, produce quality, and profits and ensure better livelihoods to the farming community. IFFCO has already reoriented its promotional programs to address current issues of soil health management to break stagnation/decline in crop productivity and enhance farmersâ€™ profits through its â€œSave the Soil Missionâ€. The Cooperatives which are not involved in the Governmentâ€™s agriculture and allied sector development projects, need to be included and reasonably supported.